Analisis Pengaruh Current Ratio (CR) dan Debt To Equity Ratio (DER) Terhadap Return On Investment (ROI) Pada PT. Globe Kita Terang, Tbk Periode 2017-2021 - Asrul; Yohana Ropati Pardede (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
The background of the problem that occurred in this study is where the Current Ratio (CR) and Debt To Equity Ratio (DER) are still below industry standards, thus affecting Return On Investment (ROI) and causing no profit to be obtained by the company from 2017 to 2017. 2021. This study aims to determine the effect of the Current Ratio (CR) and Debt To Equity Ratio (DER) on Return On Investment (ROI). This research is a quantitative data with the type of explanatory research that explains the relationship or influence between variables. This study uses secondary data obtained from the annual financial reports of PT. Globe Kita Terang, Tbk for the 2017-2021 period which is listed on the Indonesia Stock Exchange (IDX). The analysis used in this research is simple linear regression, multiple linear regression, simple linear correlation, and multiple linear correlation. The independent variables in this study are Current Ratio (CR) and Debt To Equity Ratio (DER) and the dependent variable in this study is Return On Investment (ROI). In conclusion, the result of the simple regression equation Current Ratio (X1) to Return On Investment (Y) is Y = -545.70 + 44.55X1. Then the calculation results from the simple regression equation Debt To Equity Ratio (X2) to Return On Investment (Y) is Y = -7001.75 – 64.71X2. And the calculation results from the multiple regression equation Current Ratio (X1) and Debt To Equity Ratio (X2) to Return On Investment (Y) is Y = -0.742 + 48.16X1 + 5.46X2. Then the result of the simple correlation equation between the Current Ratio (X1) to Return On Investment (Y) is 0.9599. Then the calculation results from the simple correlation equation Debt To Equity Ratio (X2) to Return On Investment (Y) is -0.9441. And the calculation results from the multiple correlation equation Current Ratio (X1) and Debt To Equity Ratio (X2) simultaneously to Return On Investment (Y) is 0.975. The results of this calculation prove that the Current Ratio (X1) has a positive and significant effect on Return On Investment (Y) and the Debt To Equity Ratio (X2) has a negative and significant effect on Return On Investment (Y). Meanwhile, simultaneously Current Ratio (X1) and Debt To Equity Ratio (X2) have a positive and significant effect on Return On Investment (Y). Based on the calculation of the coefficient of determination Current Ratio (X1) and Debt To Equity Ratio (X2) simultaneously contribute or influence the Return On Investment (Y) of 95.06% while the remaining 4.94% (100% -95.06% ) is the influence of other variables that are not used in this study.